Experiences of Accreditation of Medical Education in Taiwan - Chi-Wan Lai (Journal of Educational Evaluation for Health Professions, 2009)
This review aims to introduce the Taiwanese Medical Accreditation System: its history, role and future goals. In 1999, the Ministry of Education, Taiwanese Government commissioned the non-profit National Health Research Institutes (NHRI) to develop a new medical accreditation system. According to that policy, the Taiwan Medical Accreditation Council (TMAC) was established in the same year. The council serves a similar function to that of the Liaison Committee on Medical Education (LCME) of the United States and the Australian Medical Council (AMC). The accreditation process consists of a self-assessment plus a four-day site visit by a team of eight medical educators that are headed by one of the council members of the TMAC. The first cycle of initial visits was completed from 2001 to 2004. Subsequent follow-up visits were arranged according to the results of the survey with smaller-sized teams and shorter periods. There is evidence to suggest that the majority (seven of eleven) of the medical schools in Taiwan have made good progress. TMAC’s next step will be to monitor the progress and raise the standard of medical education in individual schools with a homogenous, superior standard of medical education.